Impact Of Biofertilizers On Growth, Nutrient Uptake, Yield, Metabolism And Rhizosphere Enzyme Activities Of Pomegranate (Punica Granatum L.) Cv. ‘kandhari Kabuli’ (Applied Biological Research, 2012)
Nursery and field experiments were carried out to assess the effectiveness  of N2-fixing bacteria, phosphate solubilizing bacteria and arbuscular  mycorrhizal (AM) fungi, alone or in combination, on the growth and  biomass production of pomegranate (Punica granatum). The study  revealed significant improvement in nursery seedlings growth by  biofertilizers use. Combined treatment of Azotobacter chroococcum +  Glomus mosseae proved most effective in enhancing the rhizosphere  microbial activity and concentration of various metabolites and nutrients  in pomegranate in nursery experiments as well as helped in better plant  establishment under field conditions. A significant improvement in plant  height and fruit yield was observed in pomegranate plants under field  conditions. Biofertilizer application also improved plant nutrient uptake  and rhizosphere microbial activities. Results indicate that biofertilizer  technology may be adopted for the establishment and development of  horticultural plant species in rainfed agro-ecosystem.
Keywords: Azotobacter; mycorrhizal fungi; pomegranate; soil enzymes; PSB; yield